Romans - Peterson, David. 1944- (Bellingham, WA : Lexham Press, 2020)
"Of all of Paul's letters, Romans is the one most immersed in the Old Testament. David G. Peterson situates Romans within the grand redemptive story of the Bible: creation, sin, Abraham's call and covenant, Israel's reception of and failure to keep the law, and God's great promises of salvation. Peterson reads Romans as Paul's exposition and defense of the gospel with unique theological insights into the Trinity, righteousness and justification, Israel and the church, apostolic ministry, and true worship and holy living. The Evangelical Biblical Theology Commentary (EBTC) series locates each biblical book within redemptive history and illuminates its unique theological contributions. All EBTC volumes feature informed exegetical treatment of the biblical book and thorough discussion of its most important theological themes in relation to the canon-all in a style that is useful and accessible to students of Scripture"--
Minimal Level Cataloging Plus.
Includes bibliographical references (pages 555-568) and indexes.
Keywords: Bible. -- Commentaries; Commentaries